PENERAPAN METODE ANALYTICAL HIERARCHY PROCESS ( AHP ) PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN MAHASISWA BERPRESTASI MENGGUNAKAN FRAMEWORK LARAVEL (STUDI KASUS : INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA) - Ebedia Hilda Am; Erna Kumalasari N; Rr. Yuliana Rachmawati K (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2015)
Outstanding Student Selection is one of the activities which is held once every year in AKPRIND Institute of Science & Technology Yogyakarta. The first winner will be sent to the Kopertis level. Outstanding Student Selection process that has lasted still not use computerized system. One of the systems that can be applied is the decision support system with a method and a tool. The method that implemented in this system is Analytical Hierarchy Process (AHP) method. This method chosen because it can break a complex problem into sub-sub problems and arrange it to an hierarchy. The tool that used in this system is Laravel framework. This Decision Support System in Outstanding Student Selection can help Administration of Student and Alumnus Bureau with the result of the calculation that applying AHP method and the result of the calculation that applying Mawapres Sarjana 2015 guide. Decision Support System in Outstanding Student Selection is a system that could support the decision making process. This system is expected to make the decision making process more easy and faster.